PERFORMA MICROFRAMEWORK PHP PADA REST API MENGGUNAKAN METODE LOAD TESTING - Indra Yatini; F. Wiwiek Nurwiyati; Khairul Anam (Jurnal Informatika Komputer, Bisnis dan Manajemen, 2021)
The need for flexibility in application development by minimizing the constraints of a server production environment makes n-tier architectures increasingly used. This architecture is implemented in the form of middleware or often called API. REST API is an API architecture that is currently the most widely used for middleware-based application development. PHP is an easy-to-use programming language for developing REST APIs with its microframework. Each microframework has features such as database connection handling, URL routing, and performance is the top one. The large number of PHP microframeworks with different performance issues makes the selection of API-based application development cores very important. Especially if it is projected to handle data exchange or client requests in large numbers. As a basis for selection, performance testing needs to be carried out on each microframework to determine its suitability for API-based application development. Performance testing uses the load testing method and develops the popular PHP microframework as a basis for creating test applications. The microframework includes FatFree, Lumen, Phalcon-micro, and Slim. Testing is carried out systematically using a test plan that has been designed for performance testing needs. The focus is to analyze the RPS (Request Per Seconds) and latency to the percentile that the wrk2 test tool generates on a predetermined test type